Faktor-Faktor Penentu Adopsi Perbankan Digital Islam di Bawah Mandat Regulasi Syariah: Bukti dari Aceh, Indonesia - Husain, Putri; Warsito, Chandra (Jurnal Ilmiah Ekonomi Islam, 2026)
This study investigates the socio-technical determinants of Islamic digital banking adoption under the unique framework of Aceh’s Sharia Financial Institutions Qanun (Qanun LKS). While this mandate achieved 100% administrative migration, its impact on substantive digital behavior remains under-explored. This research addresses the "Adoption Paradox" where high legal inclusion fails to trigger active usage. A quantitative descriptive-analytical design was employed, surveying 200 Bank Syariah Indonesia (BSI) customers in Bireuen Regency, a semi-rural district, to capture digital transition challenges in a traditional society. Data were analyzed using Multiple Linear Regression in SPSS 21. Findings reveal a significant adoption gap, with only 30% of respondents classified as active users. Regression results indicate that Digital Literacy is the strongest predictor (β = 0.600; p < 0.001), followed by Trust in Security (β = 0.462; p < 0.001), perceived ease of use, and social influence. The study concludes that top-down legal mandates are insufficient without bottom-up interventions in digital capability and trust-building. To achieve the Cost Optimization Rate (COR), Islamic financial institutions must prioritize cybersecurity and literacy programs to bridge the adoption gap. This research contributes by linking region-specific Sharia mandates with technology acceptance models, offering a scalable framework for digital transformation in Sharia-governed economies.